Risks of psychological traumatization and stress adaption of medical staff working under war conditions (analytical literature review) - M.V. Krasnoselskyi; O.O. Kyrylova; O.Ye. Dubenko; T.V. Rublova; Yu.V. Pavlichenko (Medičnì Perspektivi)
Medical and psychological consequences of war have a destructive impact on mental health during the hostilities and after their cessation and determine a wide variety of different psychogenic disorders in an individual who was in the territory of hostilities. The purpose of the work is to analyze and summarize scientific literature data on the issue of mental traumatization of the medical staff under the conditions of working during war conflicts. The article is concerned with the analytical literature review, the analysis of experience of studying features of psychoemotional state of the medical workers and people who were in the territory of hostilities, and delivering medical and psychological aid to them. The features of psychological responsiveness of the individuals who participated in war conflicts and possible consequences of mental health damage are described. Scientific data on mental state of medical staff working under the conditions of the war conflict are limited. Most studies are concerned with military personnel and civilians. During war conflicts, medical workers face with chronic stress factors and take their own personal risk that may lead to deterioration of mental health, including post-traumatic stress disorder. International studies have shown that, regardless of the specialty, doctors who are working in stress situations, including war, have an increased risk of depression compared to civil population in general due to high risk of burnout. The incidence of depression among doctors ranges from 11% to 47%. Military medics can suffer severe stress due to the increased risk of death or injuries of other people, and they are also directly or indirectly impacted by a common traumatic reality. The impact of injuries, deaths, sexual assaults, and personal threats jeopardize health of combat nurses who participate in military, humanitarian, and aid missions after natural disasters. As a result, they suffer from unfavorable mental consequences. Compassion fatigue, exhaustion, and post-traumatic stress disorder are common. The importance of medical and psychological aid aimed at decreasing stress and stabilizing psychoemotional state of the medical staff who are working under the conditions of war led to development of a large number of programs in various psychotherapeutic areas that have shown their high effectiveness.